Real‐world drug survival of Brodalumab, in patients with psoriasis switched from Ixekizumab: Results of a single centre retrospective study (BroSwitch) - Jolijn C. Bethlem; Jenny A. H. M. Janssens; Milan Tjioe (Wiley, 2023)
Abstract Background Biologicals are a widely used treatment for psoriasis (PsO), however, biologicals are expensive and while continuous use is warranted, sometimes need switching. In January 2021, dermatologists of Bravis Hospital and dermaTeam clinic actively switched 91 patients, who received Ixekizumab, to Brodalumab due to health economic reasons. This is a retrospective, real‐world cohort study. Objectives This study aimed to assess Brodalumab drug survival, reasons for discontinuing Brodalumab and side effects. The researchers also hoped to gain insight into determinants for Brodalumab drug survival. Methods Data were retrospectively extracted from electronic medical records (EMR). Psoriasis Area Severity Index (PASI) scores were evaluated. Drug survival was analysed using Kaplan-Meier estimates. Analyses were split according to the reason for discontinuing: primary or secondary ineffectiveness, and side effects. Results A total of 91 EMRs were included. Overall, 29 patients (32%) discontinued Brodalumab within 1 year owing to: primary inefficacy (45%), secondary inefficacy (31%), only side effects (14%), or other reasons (10%). The most reported side effect was xerosis cutis, followed by joint pain. PASI scores were lacking. No determinants to make switching more successful were found. Drug survival was 53% at Week 50. Conclusions Drug survival of Brodalumab after switch from Ixekizumab in our patient group was low at 53%. Inadequate disease control was more important than side effects.